“I was ashamed, and now I am proud as I finally know how to let go.” How Female Polers Perceive, Experience, and Give Meanings to Their Bodies—An Ethnographic Case Study - Wojciechowska, Magdalena (Qualitative Sociology Review, 2023)
Although the popularity of recreational pole dancing continues to gain momentum, its prevailing association with the erotic sphere and resulting stereotypes shape it as a borderline activity. Notably, the way pole dancing is approached and enacted elucidates how bodies, especially female embodiment, are socially constructed and controlled. Thus, to look at that issue from recreational female polers’ perspectives, this article sheds light on how their understandings of the body evolve with their engagement in the leisure activity at hand. That process is analyzed in the context of how women deal with tensions that arise while they navigate between the internalized societal expectations concerning desired femininity and personal agency. Drawing on ethnographic and interview data from pole dance studios in Poland, I discuss how polers’ perspectives on their bodies change from personal and interactional ‘limitations’ to embracing their bodies as interactional partners with whom to achieve their goals. In the process of learning by doing, women get to know their bodies and develop with them a relationship based on trust. Subsequently, growing to understand the bodies as their substantial selves that functionality allows them to achieve the ‘impossible’ as one empowers women. At the same time, I highlight how the process of espousing alternative perceptions of one’s body unfolds under the umbrella of an internalized frame of meanings concerning female embodiment that lures women to fit societal expectations. The interplay between the two sheds light on how female polers navigate toward reclaiming their self-confidence from the clutches of the critical social gaze while negotiating the notion of their bodies. Compelling in that regard is how relying on erotic associations with recreational pole dancing in terms of inciting empowerment through a sexual agency, as some studios do, plays out and factors into female pole dancers’ experiences concerning their leisure activity.